MODELING AS A METHOD OF ENTERPRISE'S ACCOUNTING POLICY FORMATION - В. Д. Кубік (Ринкова економіка: сучасна теорія і практика управління)
The article is devoted to the issues of accounting policy modeling of enterprise activities in the field of management. Modeling as a method brings variance into enterprise accounting policy, promoting qualitative analysis of normative legal accounting documents and stimulating the choice of the most optimal model of executive’s order concerning accounting policy. In the course of the given research the existing approaches to the basic concepts of modeling are analyzed. The analysis of the essence and the role of accounting policy as a model of a system of accounting, control and economic analysis, and, in the broader sense – the whole system of enterprise economy management – convinces that these two systems should develop, focusing on the aims of the managing system in order to achieve the required condition of the object of management. Accounting policy development requires not only specific, accounting-based principles, but general management principles as well. Implementing modeling method in the process of enterprise accounting policy defining makes it possible to reduce expected expenses, to create an advantageous ground for making managerial decisions, and also to provide an opportunity to identify the best variation of the modeled object functioning, as the regulations of the international accounting system implies substantial impact of accounting policy on the formation of enterprise activity results.